Biogeography and diversification of Rhegmatorhina (Aves: Thamnophilidae): Implications for the evolution of Amazonian landscapes during the Quaternary. (17th January 2018) - Ribas, Camila C.; Aleixo, Alexandre; Gubili, Chrysoula; d'Horta, Fernando M.; Brumfield, Robb T.; Cracraft, Joel
Abstract: Aim: To test the importance of alternative diversification drivers and biogeographical processes for the evolution of Amazonian upland forest birds through a densely sampled analysis of diversification of the endemic Amazonian genus Rhegmatorhina at multiple taxonomic and temporal scales. Location: Amazonia. Taxon: Antbirds (Thamnophilidae). Methods: We sequenced four mtDNA and nuclear gene regions of 120 individuals from 50 localities representing all recognized species and subspecies of the genus. We performed molecular phylogenetic analyses using both gene tree and species tree methods, molecular dating analysis and estimated population demographic history and gene flow. Results: Dense sampling throughout the distribution of Rhegmatorhina revealed that the main Amazonian rivers delimit the geographic distribution of taxa as inferred from mtDNA lineages. Molecular phylogenetic analyses resulted in a strongly supported phylogenetic hypothesis for the genus, with two main clades currently separated by the Madeira River. Molecular dating analysis indicated diversification during the Quaternary. Reconstruction of recent demographic history of populations revealed a trend for population expansion in eastern Amazonia and stability in the west. Estimates of gene flow corroborate the possibility that migration after divergence had some influence on the current patterns of diversity. Main Conclusions: Based on broad‐scale sampling, a clarification of taxonomic boundaries, and strongly supported phylogenetic relationships, we confirm that, first, mitochondrial lineages within this upland forest Amazonian bird genus agree with spatial patterns known for decades based on phenotypes, and second, that most lineages are geographically delimited by the large Amazonian rivers. The association between past demographic changes related to palaeoclimatic cycles and the historically varying strength and size of rivers as barriers to dispersal may be the path to the answer to the long‐standing question of identifying the main drivers of Amazonian diversification.